WHAT ARE THE DETERMINANTS OF CONSUMERS' ONLINE REVIEWS ADOPTION FOR HOTEL BOOKINGS: A STRUCTURAL EQUATION MODELLING APPROACH - Suman Lata; Krishma Rana (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2021)
Experienced travelers share their reviews regarding hotel services which serve as a testimony for novice travelers and help them to make their decision whether to book that hotel or not. The current study aims to identify the various factors affecting the intentions of travelers for online hotel bookings. Data was collected from 419 respondents who adopt online reviews published on online travel aggregators for online hotel bookings. The respondents for this study are taken from Delhi. Further, the hypotheses of this study were validated with the help of structural equation modeling (SEM) using partial least squares (PLS). The paper found Information quality; Source credibility, Information sidedness, and Information consistency are the significant predictor of traveler’s Information usefulness for hotel bookings. Further, the relationship between Information usefulness and online hotel bookings intentions was also found statically significant. This study has provided implications for hotel managers that hotel managers should continue to monitor the negative reviews and take some necessary actions to overcome these issues. As well as they should focus on their service quality which helps them to make their customers happy and encourage them to upload positive reviews. This study analyzed the travelers’ adoption of user[1]generated reviews from online travel aggregators for online hotel bookings by using an information adoption model with additional constructs.